PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL) DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2015 – 2017 - Christian Harrison (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
Banking companies can endure the competition in the business world and can be a good example for companies in other industries in maintaining firm value in the eyes of investors. The variables tested in this study consisted of company values measured using Tobin's Q ratio, good corporate governance mechanism proxied through institutional ownership, audit committee, the board of commissioners, managerial ownership, independent commissioners, and the size of the board of directors, measured loan to deposit ratio with the percentage of lending loans with third-party funds, non-performing loans as measured by the percentage of non-performing loans compared to lending, and the size of the company as measured by the total assets owned by the company. The research sample is a banking company that is listed on the Indonesia Stock Exchange (IDX) in 2015-2017. This study uses a purposive sampling method in determining the number of samples used and obtained 39 companies used as samples. While the method of data analysis uses the classical assumption test, hypothesis testing, and multiple linear regression analysis. The results of this study indicate that the mechanism of good corporate governance has a significant effect on firm value while the loan to deposit ratio, non-performing loans, and firm size have no significant effect on firm value. Keywords: Firm value, good corporate governance, institutional ownership, audit committee, the board of commissioners, managerial ownership, independent commissioner, size of the board of directors, loan to deposit ratio, non-performing loans, company size.